2004
DOI: 10.1136/vr.154.22.687
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of heart rate variability in cattle fed BSE‐infected material

Abstract: The brainstem is the region of the brain of cattle with the highest concentration of the abnormal prion protein associated with bovine spongiform encephalopathy (BSE), and specific nuclei in the medulla oblongata of the brainstem, which exhibit changes as a result of the disease, are involved in the modulation of heart rate variability (HRV). The low- and high-frequency components of the HRV of 48 control cattle, 43 cattle fed 1 g of brain homogenate from BSE field cases and 42 cattle fed 100 g of brain homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 14 publications
0
21
1
1
Order By: Relevance
“…Different types of Holter recorders (Konold et al, 2011) and fixed (Little et al, 1996;Pomfrett et al, 2004) or telemetric systems (Lefcourt et al, 1999) as well as portable HR monitors have been used to investigate HR and HRV in dairy cattle ( Table 1). The latter ones were originally developed for human athletes and sport medicine research (von Borell et al, 2007b) but these models do not record and store the whole electrocardiogram, only the interbeat intervals (IBIs) (Hopster and Blokhuis, 1994).…”
Section: Methods Of Measurement and Analysis Of Hr And Hrv In Dairy Cmentioning
confidence: 99%
See 3 more Smart Citations
“…Different types of Holter recorders (Konold et al, 2011) and fixed (Little et al, 1996;Pomfrett et al, 2004) or telemetric systems (Lefcourt et al, 1999) as well as portable HR monitors have been used to investigate HR and HRV in dairy cattle ( Table 1). The latter ones were originally developed for human athletes and sport medicine research (von Borell et al, 2007b) but these models do not record and store the whole electrocardiogram, only the interbeat intervals (IBIs) (Hopster and Blokhuis, 1994).…”
Section: Methods Of Measurement and Analysis Of Hr And Hrv In Dairy Cmentioning
confidence: 99%
“…Research demonstrated a significant shift in the activity of the autonomic nervous system reflected in HRV in relation with certain infectious diseases. Studies detected the predominance of the vagal tone experiencing the radical increase of RMSSD (Pomfrett et al, 2004) or HF power (Little et al, 1996), whereas others described bradycardia (Winter et al, 1989;Austin et al, 1997) in cows positive for bovine spongiform encephalopathy (BSE).…”
Section: Effect Of Pathological Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…The test is simple in that an ECG monitor and a simple breathing monitor is fitted to the animal and the full test can be carried out within minutes. More recently, Pomfrett et al [85] investigated autonomic nervous system activity by analysis of low-and high-frequency heart rate variability (HRV) in control cattle and cattle challenged with either 1 g or 100 g of BSE infected material. They reported a significant difference in the level of high-frequency HRV between control cattle and cattle dosed with 1 g or 100 g of BSE-infected brain material.…”
Section: Electrophysiological Markers and Imagingmentioning
confidence: 99%